PUBLIC AFFAIRS MANAGEMENT PLAN PROGRESS REPORT SEPTEMBER 1989 - SCHOONMAKER, DEBBIE; HRYCAJ, CAROL; LYONS, JOHN; RANSOME, SHARON; THOMAS, KAREN; PANZER, FRED; BRUCE, JANET; FERNICOLA, KAREN; DAWSON, BRENNAN; GLEASON, M; STUNTZ, SUSAN; CANNELL, ANNE; BOOTH, M (Tufts Archival Research Center, 2007)
Marginalia; Confidential; Progress Report from September 1989 highlighting issues such as excise tax, public smoking, smoking on airlines, effectiveness of advertising campaigns, fire safety, social costs, and media relations. States future goals in each of these areas, as well as summarizing results of the prior year's activities.